A nationwide dataset of stable isotopes in meteoric and terrestrial water across Peru - Romero, Carol (2025)
Water Stable Isotopes (δ18O, δ2H) are valuable tools for tracing sources and interactions in the water cycle, providing important information dedicated to understanding physical mechanisms related to global climate. Despite their significance, the topic of isotopic research in South America has been hindered by limited data. To address this gap, we launched a national-level water stable isotope dataset covering different water sources in Peru (WSI-PeruDB). The dataset contains curated in-house data and incorporates previously published records from various locations collected between 2000 and 2021. The WSIPeruDB dataset is composed of 489 water collection sites and allows a comprehensive use of the dataset by implementing standardized metadata templates containing essential geographical information such as latitude, longitude, and altitude (from sea level to 5000 m a.s.l), and sampling information such as sample type (e.g. groundwater, precipitation, river, spring, and others) and sampling frequency (e.g. biweekly, daily, monthly). The WSIPeruDB dataset is publicly available on Zenodo, facilitating access and use for the scientific community.